Pengaruh Content Marketing (Shopee), Review Product, dan Brand Ambassador Terhadap keputusan Pembelian Produk Scarlett Whitening pda Mahasiswa Universitas PGRI Kanjuruhan Malang - Febiana, Febiana; Nurfarida, Iva Nurdiana; Kowiyanto, Kowiyanto; Suharso, Arien Anjar Puspitosari (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2025)
This study aims to explore the ways in which product reviews, brand ambassadors, and content marketing on Shopee influence users’ choice to purchase Scarlett Whitening products. A total of 112 participants were given a Google Form to fill in to collect data for this study. Purposive sampling is one of the sampling strategies, and quantitative explanatory research falls into this group. Conventional assumptions, multiple linear regression, descriptive statistics, and hypotheses are part of the data analysis methods using SPSS 22.0 software. According to recent research, brand ambassadors, product reviews, and content marketing have a positive and substantial impact on customer purchase choices (Shopee). Shopee, a component of content marketing, has a constructive and substantial impact on purchase choices. However, product reviews and brand ambassadors do not significantly influence what consumers choose to buy.